Argon vs Nitrogen: what is the most effective gas for shelf-life extension of buckler sorrel? - Pinela, José (2022)
Buckler sorrel (Rumex induratus Boiss. & Reut.; Polygonaceae) is an underutilized leafy vegetable with peculiar sensory properties and potential as a gourmet food product. In the food industry, different packaging methods have been used for shelf-life extension, but it is important to know how the quality of minimally processed vegetable is affected by these treatments. Recently, nitrogen and argon have been used for food packaging. Nitrogen is low soluble in water and other food constituents and does not support the growth of aerobic microbes. In turn, argon is biochemically active and appears to interfere with enzymatic oxygen receptor sites. Herein, modified atmospheres enriched with nitrogen and argon were evaluated for shelf-life extension of buckler sorrel leaves.